2014
DOI: 10.1016/j.actatropica.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

An agent-based model driven by tropical rainfall to understand the spatio-temporal heterogeneity of a chikungunya outbreak

Abstract: Vector-borne diseases, such as dengue, malaria and chikungunya, are increasing across their traditional ranges and continuing to infiltrate new, previously unaffected, regions. The spatio-temporal evolution of these diseases is determined by the interaction of the host and vector, which is strongly dependent on social structures and mobility patterns. We develop an agent-based model (ABM), in which each individual is explicitly represented and vector populations are linked to precipitation estimates in a tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…The bimodal nature of the outbreak was captured by two studies: Bacaër, by assuming a hypothetical periodic vector abundance [96], and Dommar et al , although only a qualitative fit was reported, by assuming rainfall dependence [98]. …”
Section: Resultsmentioning
confidence: 99%
“…The bimodal nature of the outbreak was captured by two studies: Bacaër, by assuming a hypothetical periodic vector abundance [96], and Dommar et al , although only a qualitative fit was reported, by assuming rainfall dependence [98]. …”
Section: Resultsmentioning
confidence: 99%
“…Such models are already available for some other vector-borne diseases (Dommar et al, 2014;Favier et al, 2005;Prosper et al, 2012). In view of the ambitious elimination target, it is now timely to include this in models for lymphatic filariasis.…”
Section: Spatial Heterogeneities In the Spread Of Infectionmentioning
confidence: 97%
“…A wide range of modeling approaches, including ordinary and partial differential equations (ODE and PDE) (Enduri and Jolad, 2014; Aldila et al, 2013) as well as agent/individual-based models have also been applied to these questions (Li and Zou, 2009; Isidoro et al, 2011; Chao et al, 2012; Dommar et al, 2014; Manore et al, 2015). Common goals for many of these modeling efforts have been to make quantitative predictions of disease dynamics and to estimate the underlying mechanistic parameters (Chowell et al, 2007; Khan et al, 2014; Ferguson et al, 2016a; Perkins et al, 2016; Johnson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%